Index - Garmaz, Jadranka (Zbornik radova međunarodnog teološkog skupa KBF-a u Splitu, 2018)
Summary according to one’s own self-explanation, evolutionary ethics is a biological theory, derived from theory of evolution, whose task is a scientific explanation of the genesis of morality phenomenon. While philosophical ethics tries, on the basis of practical mind, to institute the validity of morality as of what needs to be, evolutionary ethics, as radical naturalistic theory, deals with the issue of what on the empirical level of actual behaviour is. Here we are trying to critically discuss the basic presumptions and deficiencies of evolutionary ethics and to point at unavoidable contents of any sensible ethical theory